Unlocking the Nexus Between Green Financing, Net Zero Roadmaps, and Science-Based Targets Initiatives in Indonesia's Infrastructure Sector - Nathania Adella Panjaitan; Yunieta Anny Nainggolan (Journal Integration of Management Studies, 2025)
Infrastructure sectors, especially energy, construction, and transport, are pivotal to Indonesia's net-zero transition due to their emissions intensity and capital demands. This study investigates how Science-Based Targets Initiatives (SBTi) disclosures and financial health affect green finance uptake. Using a mixed-method approach and logistic regression on 65 IDX-listed infrastructure firms within the 2023 fiscal year, this research incorporates firm-level data from annual and sustainability reports. It applies indicators including Return on Equity (ROE), Debt-to-Equity Ratio (DER), Cost of Debt (COD), and SBTi-aligned disclosure scores (CNZSTot). The results show that COD is the only significant financial predictor, while SBTi disclosure scores outperform net-zero roadmap availability in explaining green finance engagement. Disclosure gaps, limited third-party assurance, and sectoral inconsistencies reduce credibility. The findings imply that formal, verifiable climate disclosures aligned with science-based frameworks are pivotal in accessing the green capital, enhancing regulatory incentives, and disclosure standards also become essential to advance Indonesia's infrastructure decarbonization agenda.